Implementation of Peer-Led Seeking Safety for Women in Jail - Kathryn M. M. Nowotny; Danielle Lee Estes; Krystle Nicole Culbertson; Ladies Empowerment and Action Program (Social Sciences)
Women are the fastest-growing segment of the incarcerated population and experience high rates of cumulative trauma exposure, mental illness, and PTSD. The aim of this study is to assess the implementation of a peer-led Seeking Safety (an evidence-based intervention for addressing trauma and addiction) pilot program for women in jail. Guided by principles from community-based participatory research and cooperative inquiry, participant surveys were analyzed (secondary data) using descriptive methods (n = 60), and qualitative interviews with program facilitators were conducted and analyzed using a general inductive approach (n = 7). Peer-led Seeking Safety is feasible, acceptable, and appropriate for women in jail, with high levels of participant satisfaction. We describe several “lessons learned” related to the jail context, including structure and security processes and vicarious and retraumatization experiences among facilitators. Preventing facilitator burnout is necessary for the sustainability of the program. Future implementations of Seeking Safety in jails should consider the lessons learned in this study.